Zoneamento ambiental e programas de manejo como instrumentos norteadores para a elaboração do plano de manejo do Parque Nacional dos Campos Gerais - Souza, Lilian Aparecida de (2022)
Created in 2006 through Decree 10,796, the Campos Gerais National Park (CGNP), located between the municipalities of Ponta Grossa, Carambeí and Castro, in the Paraná State, faces a process of environmental degradation, due to the socioeconomic activities in the vast majority associated with agriculture, enhanced by the absence of management plan. Thus, the present research had the general objective of elaborate a proposal for environmental zoning, together with biodiversity management programs. Its development of the proposal took place through three stages: i) the bibliographic review; ii) elaboration and organization of the comparative results on a time scale with images from the LANDASAT 5 satellites of the years 2011, 2016 and 2021, through vector and matrix data in the program of QGis georeferencing for land use and land cover; and iii) the proposal of environmental zoning together with biodiversity management programs such as the environment management program, sustainable rural and connectivity programs for areas of environmental importance, such as the feasibility of implementing fauna passages, since the Campos Gerais National Park, has two fragments due to PR 513 that is inserted within the limits of the CGNP. The insertion of a Mosaic of Conservation Units (UCs) of Conservation Units close to the CGNP, would collaborate for the insertion of other biodiversity conservation programs such as ecological corridors and the creation of Private Reserves of Natural Heritage (PRNH) of private areas close to the park that could compose the proposed Mosaic of Conservation Units. The results obtained show an intense variation in the use and cover of the soil in the last ten years, with the decrease of the soil cover of the mixed abrophilous forest and of the non-forest soil cover, strongly influenced by the development of anthropic activities of agricultural predominance.